Power education at the crossroads. - Chowdhury, B.H (IEEE spectrum)
To meet the demands of designing and running far more complex and highly integrated electricity systems, a new kind of power engineer is needed. In this paper, the author describes how, though students tend to favor higher-tech and more lucrative fields than power engineering, reports of the discipline's demise are exaggerated